Association of Malassezia species with dandruff - Rudramurthy, Shivaprakash M. (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND & OBJECTIVES: Malassezia species implicated with dandruff vary at different geographical locations. The present study was conducted to determine the spectrum and distribution of Malassezia species in dandruff patients and healthy individuals. METHODS: Patients with dandruff from northern (Chandigarh) and southern (Manipal, Karnataka) parts of India (50 each) and healthy individuals (20) were included in the study. Dandruff severity was graded as mild, moderate and severe. Malassezia spp. isolated were quantified and identified by phenotypic characters and molecular methods including PCR-RFLP and DNA sequencing. RESULTS: Number of Malassezia spp. retrieved was significantly higher (P<0.001) in dandruff cases (84%) as compared to healthy individuals (30%). Isolation of Malassezia spp. was significantly higher (P<0.01) in patients from southern India. In moderately severe cases M. restricta was single most predominant (37.8%) isolate from patients of northern part of India and M. furfur (46.4%) from patients of southern part of India. Malassezia density was significantly associated with the severity of dandruff (P<0.001). INTERPRETATION & CONCLUSIONS: Our results on a limited number of individuals show that Malassezia spp. associated with dandruff varies in different regions of the country and the density of yeasts increases with severity of disease.